Large displacement bi-directional out-of-plane Lorentz actuator array for surface manipulation. (20th July 2017) - Park, Byoungyoul; Afsharipour, Elnaz; Chrusch, Dwayne; Shafai, Cyrus; Andersen, David; Burley, Greg
Abstract: This paper presents a large displacement out-of-plane Lorentz actuator array for surface manipulation. Actuators are formed from single crystal silicon flexible serpentine springs on either side of a rigid crossbar containing a narrow contact pillar. A rigid mounting rail system was employed to enable a 5 × 5 array, which offers scalability of the array size. Analytical and finite element models were used to optimize actuator design. Individual actuators were tested to show linear deflection response of ±150 µ m motion, using a ±14.7 mA current in the presence of a 0.48 T magnetic field. This actuator array is suitable for various 2D surface modification applications due to its large deformation with low current and temperature of operation, and narrow contact area to a target surface.